1964
DOI: 10.1038/bjc.1964.41
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Proteins by Normal and Tumour Cells In Vitro

Abstract: THE concept that rapidly growing tumours are " nitrogen traps " has led to the suggestion that plasma and other proteins may be ingested intact by tumour cells to a much greater extent than by most normal cells (Henderson and LePage, 1959; Gey, 1956). Ingestion is generally assumed to occur by the process of pinocytosis, and increased pinocytotic activity would be consistent with increased cell surface activity of tumour cells which might be expected from their decreased adhesiveness (McCutcheon, Coman and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 13 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…As far back as the 1960s, several research groups reported that human ferritin could be selectively taken up by tumor cells . Then, in the 1980s, Fargion et al found that H‐ferritin specifically binds to a protein of ∼100 kDa molecular weight .…”
Section: The Ferritin Receptormentioning
confidence: 99%
“…As far back as the 1960s, several research groups reported that human ferritin could be selectively taken up by tumor cells . Then, in the 1980s, Fargion et al found that H‐ferritin specifically binds to a protein of ∼100 kDa molecular weight .…”
Section: The Ferritin Receptormentioning
confidence: 99%
“…Specific accumulation of liposomes in tumours, and particularly in tumour cells, would be of considerable advantage in improving the selectivity of anti-cancer drugs. Such a possibility seems feasible in view of reports that some tumour cells have a high endocytic activity (Busch et al, 1961;Ghose et al, 1962;Easty et al, 1964;Mego & McQueen, 1965;Trouet et al, 1972) which may enhance uptake of liposomes. Previous studies with animal models have shown that tumour localization of liposome markers is possible by a careful selection of the size and membrane properties of the liposome (Dapergolas et al, 1976;Richardson et al, 1977Richardson et al, , 1978b.…”
mentioning
confidence: 99%
“…Busch and Starbuck (1964), after injections of proteins labelled with radioactive isotopes, found that the specific activity of the protein within the tumour was higher than that in the liver and other normal tissues studied. Easty, Yarnell, and Andrews (1964) found that several tumour cell types, cultured in vitro, showed considerable uptake of fluorescein-labelled proteins. Ghose, Nairn, and Fothergill (1962) found in vivo a substantial amount of protein conjugate taken up by cells of ascites and solid tumours, although Easty (1964) has reported that uptake of fluorescent proteins into tumours in vivo frequently involves macrophages and stroma.…”
Section: Pinocytosis In Tumour Cells and Its Possible Application In mentioning
confidence: 99%